NTU-JTC feasibility studies on vanadium-redox flow batteries (VRB) for energy storage in buildings - Narayanan Siddharth (2014)
The electrical transmission in place in today’s world is rapidly undergoing a change with the inclusion of renewable sources of energy for multiple sources of energy production away from the conventional system of energy production. Energy storage devices like Redox flow batteries (example: Vanadium Redox battery) have become increasingly important in this scenario. As a result, there is a pertinent need to study these systems to understand the behavior as accurately as possible to get the best possible output out of it. In the first part, the influence of temperature on the capacity of the battery is studied by modelling the diffusion of different species of Vanadium ions across the ion exchange membrane and calculating the capacity decay due to resulting self-discharge. It was seen that the capacity loss had two parts to it, one contributed by the intrinsic loss due to the rise in temperature and the second part due to the diffusion process. The effect of temperature was seen to be the most in the first half of the process with the effects stabilizing towards the end. In the second part, the charging model of the Vanadium Redox battery was studied by applying the Constant Current- Constant Voltage algorithm and modelling for different SOC limits for the Constant current charging mode across a current range of 30 to 58 Amperes. It was found that the efficiency increased with increasing SOC limit with the rate of increase decreasing for every increase in SOC limit. The optimal charging current was found to be in the corridor of 35-45 Amperes with the exact value changing depending on the defined SOC limit.